A long-term perspective on the exploitation of Lipari obsidian in central Mediterranean prehistory. (27th February 2018) - Freund, Kyle P.
Abstract: Of the four major island sources of obsidian in the central Mediterranean, Lipari raw materials have the widest distribution, being found at over 200 archaeological sites throughout mainland Italy, southern France, northern Africa, and Sicily. As a means of contextualizing the importance of Lipari obsidian within broader cultural processes, this paper discusses the long-term exploitation of the island's raw materials from the sixth to second millennia BC, in turn emphasizing the reflexive relationship between the movement of Lipari obsidian and the broader circumstances that mediated its use. Over the past 50 years, a large number of studies have been published on obsidian in the central Mediterranean, the majority of which relate to the sourcing of archaeological objects. In total, over 10, 000 artifacts have been elementally or visually characterized from well over 400 archaeological sites. Using a newly compiled database of prior obsidian studies, this paper highlights the importance of Lipari obsidian within wider networks of interaction. Through a diachronic overview of the distribution of Lipari obsidian along with a consideration of how these materials were consequently reduced and used, this paper highlights the impact of the spread of Neolithic lifeways on the establishment of large-scale obsidian circulation networks as well as the effects that shifting value regimes associated with the adoption and proliferation of metal technology had on the collapse of long-distance exchange networks. By the second millennium BC, the use of Lipari obsidian becomes a localized phenomenon largely restricted to sites on Sicily and increasingly associated with human burials. While it is easy to explain the continued use of obsidian in these areas as being the result of its ease of procurement, the last vestiges of a dying practice, this paper demonstrates that the situation is slightly more complex. In many ways, the exploitation history of Lipari obsidian mirrors that of other central Mediterranean sources. However, this paper brings to light unique factors that allowed raw materials from a relatively small Aeolian island to become an object of value throughout the entire central Mediterranean.